The role of adjuvant chemotherapy in rectal cancer patients with ypT0-2N0 after neoadjuvant chemoradiotherapy - Yang, Jianguo; Deng, Qican; Chen, Zhenzhou; Chen, Yajun; Fu, Zhongxue (Frontiers in Oncology, 2024)
Background Neoadjuvant chemoradiotherapy has emerged as the established treatment for locally advanced rectal cancer. Nevertheless, there remains a debate regarding the necessity of adjuvant chemotherapy for patients with locally advanced rectal cancer who exhibit a favorable tumor response (ypT0-2N0) after neoadjuvant chemoradiotherapy and surgery. Thus, the objective of this study is to investigate the impact of adjuvant chemotherapy on the oncological prognosis of rectal cancer patients who have a good response to neoadjuvant chemoradiotherapy. Materials and methods The study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol. Articles were searched in the Web of Science, PubMed, and Cochrane Library databases. The primary outcomes assessed were 5-year overall survival, disease-free survival, cancer-specific survival, recurrence-free survival, local recurrence, and distant metastasis. The data was summarized using a random effects model. Results A meta-analysis was conducted using 18 retrospective studies published between 2009 and 2023. The studies included 9 from China and 5 from Korea, involving a total of 6566 patients with ypT0-2N0 rectal cancer after neoadjuvant chemoradiotherapy. The pooled data revealed that adjuvant chemotherapy significantly improved 5-year overall survival (OR=1.75, 95% CI: 1.15-2.65, P=0.008), recurrence-free survival (OR=1.73, 95% CI: 1.20-2.48, P=0.003), and reduced distant metastasis (OR=0.68, 95% CI: 0.51-0.92, P=0.011). However, adjuvant chemotherapy did not have a significant effect on disease-free survival, cancer-specific survival, and local recurrence in ypT0-2N0 rectal cancer. Subgroup analysis indicated that adjuvant chemotherapy was beneficial in improving overall survival for ypT1-2N0 rectal cancer (OR=1.89, 95% CI: 1.13-3.19, P=0.003). Conclusion The findings of the meta-analysis suggest that adjuvant chemotherapy may provide benefits in terms of oncological outcomes for rectal cancer patients with ypT0-2N0 after neoadjuvant chemoradiotherapy and radical surgery. However, further prospective clinical studies are needed to confirm these findings.